Flexibility strategy and market orientation of culinary business performance of MSMEs In West Sumatra - Whyosi Septrizola; Thamrin Thamrin; Wiwiek Indrayeni (Universitas Negeri Padang, 2022)
The purpose of this research is to analyze the effect of: (1) Flexibility Strategy on the performance of culinary SMEs in West Sumatra, (2) Market orientation on the performance of culinary SMEs in West Sumatra. MSMEs engaged in the culinary field in West Sumatra are the objects that are the focus of this research. This study has a population consisting of SMEs in the culinary business in Padang, Bukittinggi, and Payakumbuh. The sample in this study was 100 MSMEs culinary business actors, with cluster random sampling data collection techniques. This research has a causative type. in this study using the Structural Equation Model (SEM) analysis tool version 2.0.